Deciphering range dynamics: effects of niche stability areas and post‐glacial colonization on alpine species distribution. (29th April 2016) - Marta, Silvio; Lacasella, Federica; Gratton, Paolo; Cesaroni, Donatella; Sbordoni, Valerio
Abstract: Aim: Niche stability areas (NSAs) are portions of the species range where climate conditions remain suitable through time. They represent the core of species ranges. Their distribution and extent, coupled with dispersal and colonization, shape the realized range of species. In this study, we quantified the roles of survival within NSAs and post‐glacial dispersal in determining the current distribution of two groups of alpine butterflies (two taxa in the Erebia tyndarus species complex; three taxa in the Parnassius apollo – P. phoebus species complex). Location: Holarctic. Methods: NSAs were identified for each taxon by combining current and past potential distributions models, estimated using different modelling techniques and general circulation models. We then (1) assessed the distributional bias towards NSAs by comparing actual occurrence records with randomized occupancies of the current potential range and (2) quantified post‐glacial dispersal by examining the distribution of distances from each occurrence record to the nearest NSA. Results: In almost all taxa, realized distributions are biased towards NSAs. However, while Erebia 's present range is strongly dominated by NSAs, some populations of Parnassius are found very far from NSAs, suggesting more effective colonization of the available geographical space. Main conclusions: Our study highlights the relative roles of survival within NSAs and post‐glacial dispersal in shaping the ranges of different alpine butterflies during the Holocene. Results suggest that Erebia was unable to disperse far from NSAs, thus experiencing increasing range fragmentation. Parnassius populations, on the other hand, coupled local survival with northward dispersal. As NSAs allowed the long‐term survival of the species, acting as sources for recolonization, and tend to preserve most of each species' genetic diversity, identifying NSAs and understanding their importance in determining the current distribution of species represents a pivotal task for the conservation of biological diversity.